Enhanced mechanical properties of PDMS/PMMA composite membrane using MWCNTs and its application in phenol separation from saline wastewater. Issue 9 (16th October 2018) - Adeel, M.; Ren, L.‐F.; Li, J.; Shao, J.; Jawad, A.; Su, C.; Wang, Y.; Guo, L.; He, Y.
ABSTRACT: This work describes the enhanced mechanical properties of composite polydimethylsiloxane/poly(methyl methacrylate) (PDMS/PMMA)/multi‐walled carbon nanotubes (MWCNTs) nanofiber membrane and its application in the phenol separation from saline wastewater. MWNCTs with varied content were immobilized in the membrane matrix using electric field of electrospinning. The neat PDMS/PMMA and composite PDMS/PMMA/MWCNTs membranes were characterized by scanning electron microscopy, universal testing machine, contact angle measurement, 3D automatic optical profiler, and pore size analyzer. Results indicated that tensile strength of composite PDMS/PMMA/MWNCTs membrane was drastically increased six times with a water contact angle (WCA) of 163.3° due to increased roughness parameters compared to neat membrane. However, porosity and fiber diameter of PDMS/PMMA/MWCTs membrane decreased with the increase of MWCNTs content. Moreover, phenol extraction efficiency of PDMS/PMMA/MWNCTs membrane was found to be 34.5% higher than neat one with similar salt rejection efficiency of 99.97%. The stability of MWCNTs in the membrane matrix was confirmed by the cross‐sectional morphology, which indicated the robust and novel design of membrane. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47123. Abstract :